Nilai-Nilai Perjuangan KH.Ahmad Dahlan yang Ditanamkan Kepada Muridnya - Dibi Nicklany; Adi Haironi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
A person's personality and character are formed in large part by their education. To develop Islamic and humanitarian ideals in Indonesia, Islamic education is crucial. KH. Ahmad Dahlan, the founder of Muhammadiyah, has had a significant influence on the growth of Islamic education in Indonesia. The goal of this research is to identify the principles that guided KH. Ahmad Dahlan's battle, comprehend the effects it had on his students, and assess how applicable these principles are in the modern world. The techniques include literature reviews, Muhammadiyah figure interviews, and historical document study. The findings demonstrate that KH. Ahmad Dahlan instills in his students characteristics like independence, diligence, self-discipline, fairness, and honesty. These principles mold the personalities of its pupils and support Indonesia's Islamic educational progress. It has been demonstrated that his pupils put these principles into practice by founding Muhammadiyah, enhancing education, and making contributions to a range of social and professional spheres. This study demonstrates how applicable KH. Ahmad Dahlan's struggle concept is today and how it can serve as a model for character education. These ideals are anticipated to create a robust, self-reliant, and morally upright generation in line with the moderate and tolerant teachings of Islam.